2001
DOI: 10.1177/0022022101032001005
|View full text |Cite
|
Sign up to set email alerts
|

How a Language Gender System Creeps into Perception

Abstract: The influence of a gender system in a language on perception was examined in a cross-cultural study. Participants were from two language groups, one with a gender system, Spanish, and the other with a limited gender system, English. In each language group, participants were from three age groups: 5-7 years old, 8-10 years old, and adult. In one experiment, participants were asked to put a typical male or female name to 20 objects. In another experiment, participants were asked to assign attributes to the objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
71
1
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 22 publications
4
71
1
10
Order By: Relevance
“…Incorporating both grammatical and stereotypical information, Flaherty (2001) found that (except for five-to seven-year-olds) there was a strong correlation in English between gender and typical attributes (gender stereotyped concepts) that were both assigned by participants to animate and inanimate objects, whereas in Spanish, gender was predominantly assigned according to the grammatical gender of the referent noun. For German, Irmen & Roßberg (2004) and Irmen (in press) provided data from reading time experiments and from eyemovement experiments that suggest additional influences of grammatical and conceptual gender.…”
mentioning
confidence: 99%
“…Incorporating both grammatical and stereotypical information, Flaherty (2001) found that (except for five-to seven-year-olds) there was a strong correlation in English between gender and typical attributes (gender stereotyped concepts) that were both assigned by participants to animate and inanimate objects, whereas in Spanish, gender was predominantly assigned according to the grammatical gender of the referent noun. For German, Irmen & Roßberg (2004) and Irmen (in press) provided data from reading time experiments and from eyemovement experiments that suggest additional influences of grammatical and conceptual gender.…”
mentioning
confidence: 99%
“…Increasing evidence suggests that grammatical gender can influence object classification (e.g. Athanasopoulos, Boutonnet 2016, Bassetti 2007, 2014, Bender et al 2016, Boroditsky, Schmidt 2000, Boutonnet et al 2012, Sera et al 1994, 2002, Flaherty 2001, Imai et al 2013, Kurinski, Sera 2011, Kurinski et al 2015, Martinez, Shatz 1996, Phillips, Borodistky 2003, Sato et al 2013, Sedlmeier et al 2016, Seigneuric et al 2007, Vigliocco et al 2004, 2005. Using different paradigms, researchers have often found a significant correlation between participants' choices and grammatical gender.…”
Section: Introductionmentioning
confidence: 99%
“…In British English, for instance, it is not unusual to refer to a ship as she and to a computer as he. Such usage is well documented and described in the literature as "opaque gender" (Flaherty 2001, Nicoladis, Fourscha-Stevenson 2011. In Estonian, such usage is not possible because the same third person pronoun (tema, short form: ta) is used to refer to both men and women (this pronoun is used mostly to refer to animate beings, but it is occasionally used to refer to inanimate objects).…”
Section: Introductionmentioning
confidence: 99%
“…German speakers rated the noun meaning "moon" (which is masculine in German, i.e., der [MASC] Mond, and feminine in Spanish, i.e., la [FEM] luna) higher in masculinity than the word for "sun" (which is feminine in German, i.e., die [FEM] Sonne, and masculine in Spanish, el [MASC] sol), whereas Spanish speakers showed the reverse pattern. Sera and colleagues (Sera, Berge, & del Castillo Pintado, 1994;Sera et al, 2002) asked Spanish and French speakers to assign either a female or a male voice to artifact objects and reported that the judgments tended to agree with the grammatical gender of the objects (see also Boroditsky, Schmidt, & Phillips, 2003;Flaherty, 2001;Ramos & Roberson, 2010). Influence of grammatical gender has been identified in tasks that do not involve explicit judgements as well (e.g., Kousta, Vinson, & Vigliocco, 2008;Vigliocco & Franck, 2001;Vigliocco, Vinson, Indefrey, Levelt, & Hellwig, 2004;Vigliocco et al, 2005).…”
Section: Introductionmentioning
confidence: 99%